(untitled) (Contemporary Mathematics, 2025)
In this paper, we integrate two foundational operators: a weighted composition operator, denoted by Wφ,ψ and two differentiation operators to construct a sandwich weighted composition operator, referred to as SWφ,ψ. We conduct a comprehensive analysis of the norms and essential norms of this operator within the framework of weighted Bloch spaces.